(untitled) (Gestión y Gerencia, 2025)
This scientific essay explores the relationship between human talent management and emotional intelligence in higher education institutions, as a useful tool for staff performance in the university context. In this sense, empirical publications on the theory of emotional intelligence, which have given rise to this area of ​​knowledge, were reviewed. The conclusive reflections indicate that human talent management supported by the postulates of emotional intelligence can develop strengthening plans in higher education institutions, through the training of workers who, by recognizing the feelings that affect them, will be able to create emotional awareness to improve their professional performance.